2003
DOI: 10.1073/pnas.2235594100
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of protease-activated receptor 1 to neuronal damage caused by transient focal cerebral ischemia

Abstract: The serine proteases tissue plasminogen activator, plasmin, and thrombin and their receptors have previously been suggested to contribute to neuronal damage in certain pathological situations. Here we demonstrate that mice lacking protease-activated receptor 1 (PAR1) have a 3.1-fold reduction in infarct volume after transient focal cerebral ischemia. Intracerebroventricular injection of PAR1 antagonist BMS-200261 reduced infarct volume 2.7-fold. There are no detectable differences between PAR1 ؊/؊ and WT mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
176
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(186 citation statements)
references
References 43 publications
8
176
1
1
Order By: Relevance
“…However, a recent study also showed that PAR4 and its agonist cathepsin G are involved in alterations of the colonic epithelial barrier in ulcerative colitis (Dabek et al, 2009). In addition, PAR1 deletion did not influence BBB disruption in the central nervous system after cerebral ischemic injury (Junge et al, 2003). Our study shows that deficiency of PAR4 prevents BBB disruption after stroke, which indicates that in the central nervous system, PAR4, instead of PAR1, has a role in the regulation of BBB function after ischemic injury.…”
Section: Par4 Deletion Attenuates Cerebral Ischemic Injurymentioning
confidence: 51%
See 1 more Smart Citation
“…However, a recent study also showed that PAR4 and its agonist cathepsin G are involved in alterations of the colonic epithelial barrier in ulcerative colitis (Dabek et al, 2009). In addition, PAR1 deletion did not influence BBB disruption in the central nervous system after cerebral ischemic injury (Junge et al, 2003). Our study shows that deficiency of PAR4 prevents BBB disruption after stroke, which indicates that in the central nervous system, PAR4, instead of PAR1, has a role in the regulation of BBB function after ischemic injury.…”
Section: Par4 Deletion Attenuates Cerebral Ischemic Injurymentioning
confidence: 51%
“…The effects of thrombin were also shown in other experimental ischemic models. Studies with PAR1 null mice and a PAR1 antagonist showed that PAR1 increases infarct volume and causes neuronal damage after both transient focal cerebral ischemia and combined cerebral hypoxia/ischemia (Junge et al, 2003;Olson et al, 2004;Sokolova and Reiser, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…77 PAR1 protein is present in both human and mouse brain, mostly in astrocytes, where it can be activated by thrombin. 78,79 More recent investigations of human GBM cell lines and short-term cultures derived from human specimens have demonstrated PAR1 expression on tumor cells. Its activation by thrombin and PAR1 agonists causes increased phospho-inositol (PI) hydrolysis and calcium mobilization, presumably coupling through Gaq.…”
Section: Tissue Factormentioning
confidence: 99%
“…Notably, in adult animals, PAR1 is expressed at moderate to high levels in brain regions involved with emotional learning, including hippocampus and amygdala (Striggow et al, 2001). PAR1 has been extensively studied for its role in coagulation and hemostasis (Coughlin, 2000;Macfarlane et al, 2001), as well as in the survival of neurons following ischemic, traumatic, or neurotoxic insults (Gingrich & Traynelis, 2000a;Shibata et al, 2001;Riewald et al, 2002;Suo et al, 2002;Cheng et al, 2003;Junge et al, 2003;Xi et al, 2003;Guo et al, 2004;Olson et al, 2004;Hamill et al, 2005;Nicole et al, 2005). Surprisingly little, however, is known about PAR1's roles in normal brain function.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin potentiation of NMDA receptor function is greatly reduced in PAR1−/− mouse hippocampal neurons (Gingrich et al, 2000b), and plasmin potentiation is blocked by BMS200261, a potent PAR1 antagonist (Mannaioni et al, 2007). In addition, endogenous brain-derived protease plasmin can activate PAR1 (Junge et al, 2003) and potentiate synaptic NMDA receptor function in brain tissue (Mannaioni et al, 2007). Taken together, these data raise the possibility that PAR1 expressed in brain parenchyma may influence learning and memory.…”
Section: Introductionmentioning
confidence: 99%